Pengakuan Human Capital Pada CV. Pusaka Bali Persada - Gede Krisna Wiguna; Nyoman Ari Surya Darmawan (Universitas Pendidikan Ganesha, 2022)
The aims of this study was to determine the recognition of human capital that carried out by CV. Pusaka Bali Persada. This research was conducted using qualitative research methods. Data were collected by applying various data collection methods, namely observation, in-depth interview, and documentation study. The data analysis technique adopted the Miles and Humbermen model which includes data collection, data reduction, data presentation, and drawing conclusions. The validity of the data in this study uses a combination of source triangulation techniques and methods. The results showed that the management of human resources applied in the CV. Pusaka Bali Persada has been well done. Human resources are considered to play an important role for the sustainability of the company. The owner's perception leads to the recognition of human capital as an asset, in this case as an investment. Based on this recognition, management can focus on managing human capital, especially in an effort to obtain, develop and maintain human capital on CV. Pusaka Bali Persada.